Dialogue, argumentation, and belief revision: a study of apologetic conversations in West Cameroon - Stephens, G. (Middlesex University / Oxford Centre for Mission Studies (OCMS), 2017)
This work studies dialogue, argumentation, and their relationship to belief revision in person-to-person apologetics in five West Cameroonian dialogues. The seeming irrelevance of Western Apologetics to West Cameroonian thought is the problem that stimulated the study. The primary methodological steps of the study include obtaining meticulously transcribed scripts of unrehearsed conversations, and subjecting those transcripts to an inquiry about the presence and nature of dialogue, argument patterns, commitment, questions, rhetoric, and belief revision in the conversations. These primary tools are drawn from Commitment in Dialogue (1995), Argumentation Schemes (2008), ‘A Truth Maintenance System’ (1979), ‘Reason Maintenance and Belief Revision’ (1992), and related sources. The initial premise, to be tested by the research, is that these conversational elements are present, and that the theories are useful in understanding the dialogues’ rationality. The second, but no less important, premise of the study is that this research contributes to an understanding of the nature and role of the cumulative case in the practice of person-to-person apologetics in West Cameroon and cultural situations dominated by relativism. Chapter 1 introduces the background of the research and the questions of the inquiry, which I call ‘tools’. Chapter 2 questions the significance of the tools and the analysis of the data for person-to-person apologetics in pluralistic contexts. Chapters 3-7 document the analysis of the dialogues. And chapter 8 ends with a summary of the evidence for the thesis of the work: ‘A belief’s entrenchment, the result of argument patterns converging into a cumulative case for the belief, is primarily sensitive to understanding and revision in the context of dialogue.’ This work contributes to the understanding of modern African rationality, and the relationships of dialogue, argument, belief revision, and the cumulative case in relativistic contexts.
free